Wavelets in the Transport Theory of Heterogeneous Reacting Solutes - Cattani, C.; Laserra, E. (Інститут гідромеханіки НАН України, 2002)
Рассматривается дисперсионное уравнение одномерной конвекции (адвекции) теории транспорта гетерогенных реагирующих растворенных веществ в пористых средах. Вейвлетное решение получено в рамках мультирезольвентного анализа. Розглядається дiсперсiйне рiвняння одновимiрної конвекцiї (адвекцiї) теорiї транспорту гетерогенних реагуючих розчинених речовин у пористих середовищах. Вейвлетний розв'язок одержано в рамках мультирезольвентного аналiзу. In this paper we consider the one-dimensional convection (advection) dispersion equation of the transport theory of heterogeneous reacting solutes in porous media. A wavelet solution is in the framework of multi-resolution analysis.